Pengaruh Komunikasi, Kompetensi dan Komitmen Terhadap Kinerja Pegawai di BPKPD Kota Banjar - Tini Rubiantini; Enas Enas; Aini Kusniawati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Less than optimal employee performance can be seen from the inefficient use of time at work. This is because certain employees act not in accordance with established rules, lack initiative and creativity in carrying out their duties, and experience poor collaboration due to inadequate communication. Carried out between superiors, subordinates and co-workers. Apart from that, the performance of employees at BPKPD Banjar City is influenced by (1) less than optimal communication. This is mainly caused by a lack of horizontal communication, which results in employees being unable to effectively coordinate tasks and resolve interpersonal problems between coworkers. Identical within the organization. (2) The competence of the Banjar City BPKPD is less than optimal due to a lack of knowledge caused by the large number of employees with low educational levels. In addition, their skills are limited in keeping up with advances in information technology, thus hampering their ability to fulfill their duties and responsibilities. (3) The level of commitment in the Banjar City BPKPD is currently less than optimal due to the low affective commitment of employees. This can be caused by their lack of participation in organizational development and their tendency to simply fulfill their job responsibilities without showing concern for the end result. The research was conducted using an explanatory quantitative survey methodology. The data analysis technique used is the Statistical Package for the Social Sciences (SPSS) application, using descriptive and regression analysis. Research findings show that (1) Communication has a positive and significant effect on employee performance at BPKPD Banjar City. This means that the better the communication, the higher the performance of employees at BPKPD Banjar City. (2) Competency has a positive and significant effect on employee performance at BPKPD Banjar City. This means that the higher the competency, the higher the performance of employees at BPKPD Banjar City. (3) Commitment has a positive and significant effect on employee performance at BPKPD Banjar City. This means that the higher the commitment, the higher the performance of employees at BPKPD Banjar City. (4) Communication, competence and commitment have a positive and significant effect on employee performance at BPKPD Banjar City. This means that the better the communication, the higher the competence and commitment, the higher the performance of employees at BPKPD Banjar City.